Aspectos motivacionais e desempenho técnico tático em praticantes de futsal com 10 e 13 anos de idade. - David, Carlos Eduardo Barros (2012)
as. Initially, was applied a questionnaire motivational sports (GAYA; CARDOSO, 1998) to 189 indoor soccer in non-competitive teams (n=108) and competitive teams (n=81), verifying the predominant factor motivating sport competence, followed by health factor and friendship / leisure. Based on the results of this questionnaire, the indoor soccer were classified into 4 groups according to participation in non-competitive or competitive teams and motivational factors: sport competence or friendship/leisure/health. The analysis of technical and tactical performance was conducted in three phases: beginning, middle and end of the season, with the application of GPAI Game Performance Assessment Instrument (OSLIN; MITCHEL; GRIFFIN, 1998) to 43 indoor soccer in the following groups: 11 soccer indoor in the non-competitive group with motivational tendency friendship/leisure/health (G1-ALS), 11 in the non-competitive group with tendency motivational sport competence (G1-CE), 10 in the competitive group with tendency motivational friendship/leisure/health (G2-ALS) and 10 in the competitive group with tendency motivational sport competence (G2-CE). Significant differences from the beginning to the end of the season in 3 groups: G2-ALS, G2-CE e G1-ALS, and at the end of the season, the group G2-CE was significantly different from the others groups. There was an association between motivation for sports and performance tactical-technical achieved over a season, with soccer players of motivational tendency sport competence with a higher gain learning in tactical-technical performance in competitive teams, and soccer players of motivational tendency friendship/leisure/health with a higher gain learning in tactical-technical performance in non-competitive teams.